PENGEMBANGAN E-LEARNING BERBASIS GOOGLE SITES UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA - Neni Citra Dewi (DIADIK, 2020)
Thisstudyaimsto: (1)producethedevelopment ofe-learningberbasisgooglesitesimprove student learningachievement  (2)describetheeffectivenessof development ofe-learning berbasisgooglesitestoimprovestudentlearningachievement.ThisstudyusesResearch andDevelopmentdesign.Thesubjects ofthis studywerestudents ofgradeXIMultimediaof SMKNegeri 2Rejang Lebong. Data collectiontechniquesusingassessmentsheetsandtests. Dataanalysisusesthe mean (t)andt-test.Theconclusionsofthisstudyare: (1)the devlopment  of e-learningberbasisgoogle  canimprovestudent achievement,and (2)the development  of e-learningberbasis googleeffectivetoincrease  learningachievement of studentsof classXI MultimediainAnimasi2D subject